Prototipe E-Klinik untuk Layanan Kesehatan Berbasis Web pada Balai Pengobatan Kantor Pusat Kementerian Pertanian - Tri Pujadi (Bina Nusantara University, 2010)
This report discusses about the administration service at House of Medicinal Treatment in Central Office of The Ministry of Agriculture Republic of Indonesia. The administration service build in a web-based system, which has changed the administration system from manual to computerized. This system, which is known as Clinic Information System, facilitate the employee at House of Medicinal Treatment when they do their medical service in clinic from patient registration, medical record and report. The conclusion of this report is that the employees in the house of medicinal treatment is assisted enough with the design of this web-based system, but the function and the accuracy of the system should still be improved.